Muslim communities in the United Kingdom, Ireland and the Benelux - Patapeika, Pavel A. (Journal of the Belarusian State University. International Relations, 2022)
This article examines the origins and evolution of Muslim communities in the United Kingdom, Ireland and the Benelux countries, selected as case examples for the region. Their Muslim communities’ characteristics and similarities are examined, along with the composition and structure of their Muslim communities. The analysis revealed several related but sometimes contradictory trends. The rise of polarisation and radicalisation coexists with the search for dialogue and interaction, and the failure of multiculturalism coincides with relatively successful integration paradigms. The study of Muslim societies in countries such as Great Britain, the Netherlands, Belgium, Luxembourg and Ireland seems very important, even urgent, for any European country.
Keywords: the United Kingdom; the Benelux; Ireland; Muslims; community; ethnicity; Islam; migration; multiculturalism; interculturalism